Occurrence of SARS-CoV-2 in Indoor Environments With Increased Circulation and Gathering of People - Dziedzinska, Radka; Kralik, Petr; Šerý, Omar (Frontiers in Public Health, 2021)
At the time of sampling (2020/2021), the number of new cases of SARS-CoV-2-positive individuals in the Czech Republic significantly exceeded the numbers in neighboring countries and in the EU. In terms of the number of deaths, the country ranked near the top of the list. Legislative orders required wearing masks indoors, disinfecting surfaces in public places, and limiting the number of people per sales area in commercial spaces. Due to an situation, most schools and shops were closed. The entire country anticipated a total lockdown. To assess the risk to public health regarding SARS-CoV-2 transmission, air and surfaces were sampled in two public places: a post office and a shopping center. Samples were also collected at the COVID-19 unit at the local hospital. Neither air nor surface samples were positive for SARS-CoV-2 virus particles in the post office or shopping center. Positive results were found in the hospital ward, with floors being the most and highest contaminated surface. Based on our results, we believe that public places do not pose a risk in relation to SARS-CoV-2 transmission, especially when epidemiological measures to reduce transmission are followed, such as wearing masks, using disinfectant or limiting the number of customers per retail establishment.